In search of artificial domatia for predatory mites. Issue 2 (1st February 2019) - Bresch, C.; Carlesso, L.; Suay, R.; Van Oudenhove, L.; Touzeau, S.; Fatnassi, H.; Ottenwaelder, L.; Paris, B.; Poncet, C.; Mailleret, L.; Messelink, G. J.; Parolin, P.
ABSTRACT: Banker plants can enhance biological pest control by providing both floral resources and appropriate oviposition sites, e.g. through acarodomatia, to predator species. The use of materials mimicking domatia i.e. artificial domatia may be an economically favourable alternative to the use of banker plants bearing domatia. The aim of the present study was to identify materials that are able to host eggs of the Neoseiulus californicus predatory mite but not those of the Tetranychus urticae pest mite. In a laboratory experiment, the oviposition of predatory and phytophagous mites were compared in Petri dishes containing leaves. The different modalities compared were (i) natural domatia of Viburnum tinus or (ii) one of twelve potential artificial domatia materials. The overall oviposition response of predatory mites to all artificial domatia was similar to that of the natural domatia. The oviposition of the Tetranychus urticae pest mite did not increase in response to the artificial domatia. Five artificial domatia hosted as many eggs of the predatory mite as observed in the natural domatia. The effect of the physical properties of artificial domatia was also tested and N. californicus was found to favour the artificial domatia that had high heat retention capacities for oviposition. Three of these artificial domatia were tested on rose plants in a greenhouse experiment; none of which enhanced the biological control on the plants under these conditions. The present study highlights the difficulty in identifying and using suitable artificial domatia as substitutes to banker plants in biological pest control efforts.